On the Safety of COVID-19 Vaccine Prophylaxis in Rheumato- logical Patients: Results and Prospects - B. S. Belov; N. V. Muravyeva; O. B. Perepechaeva (Антибиотики и Химиотерапия)
The coronavirus disease pandemic 2019 (novel coronavirus disease, COVID-19) has attracted the attention of the medical community to new clinical and fundamental problems of human disease immunopathology. Despite the lifting of the international emergency regime and the announcement of the end of the COVID-19 pandemic, the World Health Organization (WHO) stressed the need to continue supporting scientific research to improve vaccines that help reduce the spread of the virus and have prospects for widespread use. This review presents the results of recent studies on the safety of vaccination against COVID-19 in patients with rheumatic diseases (RD). In general, the frequency of exacerbation of RD after vaccination against COVID-19 seems to be quite low (5–10 %) and has no statistically significant associations with a specific vaccine or antirheumatic therapy. The prospects of using monoclonal antibodies for the purpose of pre-exposure prophylaxis of COVID-19 in patients with RD are outlined.